1984
DOI: 10.1007/bf00151327
|View full text |Cite
|
Sign up to set email alerts
|

A frequency-agile interferometer for solar microwave spectroscopy

Abstract: A high-resolution microwave spectrometer has been developed by converting the Owens Valley solar interferometer to frequency-agile operation. The system uses 27 m antennas equipped with phase-locked receivers which can change their observing frequency in 25 or 50 ms. Microwave spectra between 1 and 18 GHz are obtained in a few seconds by successive observations at up to 86 discrete frequencies. At each frequency the data are equivalent to the total power from each antenna and the interferometric amplitude and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…For comparison, the time profile of emission at 15.6 GHz, due to the well-known gyrosynchrotron mechanism, is also shown with data from the Owens Valley Solar Array (OVSA; Hurford, Read, & Zirin 1984). At the bottom is a 10 s period during peak P1, at 5 ms time resolution, showing the superposed rapid pulses with the main bulk emission subtracted.…”
Section: Introductionmentioning
confidence: 91%
“…For comparison, the time profile of emission at 15.6 GHz, due to the well-known gyrosynchrotron mechanism, is also shown with data from the Owens Valley Solar Array (OVSA; Hurford, Read, & Zirin 1984). At the bottom is a 10 s period during peak P1, at 5 ms time resolution, showing the superposed rapid pulses with the main bulk emission subtracted.…”
Section: Introductionmentioning
confidence: 91%
“…In the White event, the immeasurably low heating may perhaps not be unexpected due to the weakness of the nonthermal emission, whose radio flux did not exceed a couple of sfu even at the flare peak time. However, a comparably cold, dense flare with a radio flux more than two orders of magnitude larger has been reported by Bastian et al (2007) based on the combination of the microwave data jointly obtained with the Owens Valley Solar Array (OVSA, Hurford et al 1984;Gary & Hurford 1994), Nobeyama Radio Polarimeters (Torii et al 1979), and the Nobeyama RadioHeliograph (Nakajima et al 1994). From the detailed analysis of the radio spectral evolution and timing in the event, along with quantitative estimates of the fast electron acceleration efficiency, loss, and energy partitions, Bastian et al (2007) concluded in favor of the stochastic acceleration of electrons in this flare, waveturbulence-mediated transport of the electrons, and acceleratedelectron-driven moderate heating of the originally cold, dense plasma of the flaring loop, which was identified as the very site where the energy release and electron acceleration happened.…”
Section: Introductionmentioning
confidence: 92%
“…This is accompanied by a non-imaging radio polarimeter operating at nine fixed frequencies between 1 and 80 GHz. The Owens Valley Solar Array (OVSA) (Hurford et al 1984;Gary & Hurford 1999) has a smaller number of dishes but superior frequency coverage, operating at 86 fixed frequencies from 1 to 18 GHz. This allows the use of "frequency synthesis" (i.e., the interpretation of the measured (u,v)-plane 1 in terms of a model source spectrum) to augment the coverage in the (u,v)-plane to a certain extent.…”
Section: Radiomentioning
confidence: 99%